Effects of STAT3 polymorphisms and pharmacokinetics on the clinical outcomes of gefitinib treatment in patients with EGFR‐mutation positive non‐small cell lung cancer. (13th May 2020) - Yokota, Hayato; Sato, Kazuhiro; Sakamoto, Sho; Okuda, Yuji; Asano, Mariko; Takeda, Masahide; Nakayama, Katsutoshi; Miura, Masatomo
Abstract: What is known and objective: We investigated the correlations among signal transducer and activator of transcription 3 ( STAT3 ) rs4796793C >G polymorphism, gefitinib pharmacokinetics and clinical responses in Japanese patients with non‐small cell lung cancer receiving gefitinib therapy. Methods: Forty‐five patients were enrolled in this study. Plasma trough concentrations (C0 ) of gefitinib at the steady‐state were measured by high‐performance liquid chromatography. Results and discussion: Patients having a gefitinib C0 of at least ≥200 ng/mL had significantly longer PFS than patients having a C0 of <200 ng/mL (median [95% confidence interval (CI)] PFS: 11.0 [8.2‐13.7] and 5.3 [0.0‐12.0] months, respectively, P  = .042). There were no significant differences in PFS between patients with STAT3 rs4796793C/C and G alleles; however, patients with STAT3 rs4796793C/C having a gefitinib C0 of ≥ 200 ng/mL had significantly longer progression‐free survival (PFS) and overall survival (OS) than those with a C0 of <200 ng/mL (median [95% CI] PFS: 11.4 [4.1‐18.6] and 3.0 [0.0‐7.0] months, respectively, P  = .008; median [95% CI] OS: 20.6 [7.4‐33.7] and 12.6 [10.1‐15.1] months, respectively, P =  .042). In patients with the STAT3 rs4796793G allele, there were no significant differences in PFS and OS between the two gefitinib C0 groups. In addition, there were no significant differences in PFS or OS according to smoking, presence of proton pump inhibitor combination, or onset of side effects. What is new and conclusion: Clinical outcomes of gefitinib in patients with the STAT3 rs4796793C/C genotype depended on plasma concentrations of gefitinib. In addition to information regarding EGFR mutations, the STAT3 rs4796793C >G polymorphism and gefitinib C0 may be potential predictors of clinical outcomes after beginning of gefitinib therapy. Abstract : Kaplan‐Meier curves for PFS and OS in patients with STAT3 rs4796793C/C having a gefitinib C0 of ≥200 and <200 ng/mL. In patients with STAT3 rs4796793C/C, patients having a gefitinib C0 of ≥200 ng/mL had a significantly longer PFS and OS ( P  = .008 and .042, respectively).